Innovation in housing refurbishment through adopting a partnering approach - Roders, Martin; Straub, Ad; Gruis, Vincent (A+BE | Architecture and the Built Environment, 2015)
Housing associations own 32 % of housing stock in the Netherlands, making them major actors in maintaining and improving the quality of life in the urban environment. The building stock requires effective innovation to keep pace with the needs of today’s tenants. Moreover, the current financial circumstances and political environment have pushed housing associations to innovate in their (re)construction processes, for example by adopting a partnering approach. Several studies indicate that the implementation of innovations could benefit from partnering approaches in the construction supply chain. An evaluation of refurbishment projects that have been carried out using a partnering approach, however, indicates that the innovation process itself was seen as the major innovation and may (initially) even hamper innovations that aim to upgrade the dwelling to current standards. This effect should be taken into account when developing innovations in dwellings.